The human immune response to saliva of Phlebotomus alexandri, the vector of visceral leishmaniasis in Iraq, and its relationship to sand fly exposure and infection - Lakhal-Naouar, Ines; Mukbel, Rami; DeFraites, Robert F.; Mody, Rupal M.; Massoud, Lina N.; Shaw, Dutchabong; Co, Edgie M.; Sherwood, Jeffrey E.; Kamhawi, Shaden; Aronson, Naomi E. (PLoS neglected tropical diseases, 2021)
Background Sand fly saliva exposure plays an important role in immunity against leishmaniasis where it has mostly been associated with protection. Phlebotomus (Ph.) alexandri transmits Leishmania (L.) infantum, the causative agent of visceral leishmaniasis (VL), in Iraq. Our group recently demonstrated that 20% of Operation Iraqi Freedom (OIF) deployers had asymptomatic VL (AVL) indicative of prior infection by the parasite L. infantum. Little is known about Ph. alexandri saliva, and the human immune response to it has never been investigated. Here, we characterize the humoral and cellular immune response to vector saliva in OIF deployers naturally exposed to bites of Ph. alexandri and characterize their immunological profiles in association to AVL. Methodology/Principal findings The humoral response to Ph. alexandri salivary gland homogenate (SGH) showed that 64% of 200 OIF deployers developed an antibody response. To assess the cellular immune response to saliva, we selected a subcohort of subjects based on their post-travel (median 4 months; range 1-22 months) antibody response (SGH Antibody [Ab] positive or negative) as well as their AVL status; ten never-traveled controls were also included. Banked peripheral blood mononuclear cells (PBMC), collected ~10 years after end of deployment, were stimulated with SGH for 96 hours. The levels of IFN- [gamma], IL-6, IL-10, IL-13 and IL-17 were determined by ELISA. Our findings indicate that OIF deployers mounted a cellular response to SGH where the anti-SGH+ asymptomatic subjects developed the highest cytokine levels. Further, stimulation with SGH produced a mixture of pro-inflammatory and anti-inflammatory cytokines. Contrary to our hypothesis, we observed no correlation between the cellular immune response to Ph. alexandri SGH and prevention from asymptomatic infection with L. infantum. Conclusions/Significance As we found, although all infected deployers demonstrated persistent disease control years after deployment, this did not correlate with anti-saliva systemic cellular response. More exposure to this vector may facilitate transmission of the L. infantum parasite. Since exposure to saliva of Ph. alexandri may alter the human immune response to bites of this vector, this parameter should be taken into consideration when considering the VL risk.